Development of a balanced instrument to measure global health-related quality of life: The 13-MD - Touré, Moustapha; Lesage, Alain; Poder, Thomas G. (Frontiers in Psychiatry, 2022)
In the measurement of health-related quality of life (HRQoL), generic instruments are of interest in measuring global health. Their applicability to all patients, regardless of their health profile, allows programs comparison whether they concern the same field or not. Quality-adjusted life-year (QALY) instruments allow the best programs to emerge for more efficiency in health’s resources utilisation. Nevertheless, many differences may be perceived among the existing generic instruments relatively to their composition, where dimensions related to physical aspects of health are generally more depicted than dimensions related to mental or social aspects. The objective of this study was to develop a generic instrument that would be complete in its covered meta-dimensions and reflects, in a balanced way, important aspects of life. To this end, a Delphi procedure has been held on 4 rounds, gathering 18 participants, that is, 7 patients, 6 caregivers and 5 citizens. The structure derived from the Delphi was submitted to psychometric tests using data from an online survey involving the general population of Quebec, Canada (n=2,273). The resulting questionnaire, the 13-D, showed very satisfying psychometric properties. It is composed of 33 items with 5 to 7 levels each. The 13-D reflects, in a balanced form, the essential aspects of health by counting 5 meta-dimensions for physical health, 4 meta-dimensions for mental health, 3 meta-dimensions for social health and a last one for sexuality and intimacy.